Cellular electron tomography of the apical complex in the apicomplexan parasite Eimeria tenella shows a highly organised gateway for regulated secretion. - Alana Burrell; Virginia Marugan-Hernandez; Richard Wheeler; Flavia Moreira-Leite; David J P Ferguson; Fiona M Tomley; Sue Vaughan (PLoS Pathogens)
The apical complex of apicomplexan parasites is essential for host cell invasion and intracellular survival and as the site of regulated exocytosis from specialised secretory organelles called rhoptries and micronemes. Despite its importance, there are few data on the three-dimensional organisation and quantification of these organelles within the apical complex or how they are trafficked to this specialised region of plasma membrane for exocytosis. In coccidian apicomplexans there is an additional tubulin-containing hollow barrel structure, the conoid, which provides a structural gateway for this specialised apical secretion. Using a combination of cellular electron tomography and serial block face-scanning electron microscopy (SBF-SEM) we have reconstructed the entire apical end of Eimeria tenella sporozoites; we report a detailed dissection of the three- dimensional organisation of the conoid and show there is high curvature of the tubulin-containing fibres that might be linked to the unusual comma-shaped arrangement of protofilaments. We quantified the number and location of rhoptries and micronemes within cells and show a highly organised gateway for trafficking and docking of rhoptries, micronemes and microtubule-associated vesicles within the conoid around a set of intra-conoidal microtubules. Finally, we provide ultrastructural evidence for fusion of rhoptries directly through the parasite plasma membrane early in infection and the presence of a pore in the parasitophorous vacuole membrane, providing a structural explanation for how rhoptry proteins may be trafficked between the parasite and the host cytoplasm.